The Effect of Some Biological Fungicides and Liquid Organic Fertilizers on Sigatoka Disease on ‘Mas’ Banana Plants (Musa acuminata Colla) - Kharisma, Anugerah Iffanda; Indratmi, Dian; Ikhwan, Ali (Journal of Tropical Crop Science and Technology, 2024)
Banana (Musa acuminata Colla) is a tropical fruit with great economic potential and export prospects. According to the Directorate General of Horticulture, Ministry of Agriculture, banana production from 2009 to 2014 fluctuated due to attacks by Plant Destruction Organisms (PDO), particularly Sigatoka disease caused by the fungus Mycosphaerella musciola. This study investigated biological agents like Trichoderma sp. and Gliocladium sp., along with liquid organic fertilizers, to control the disease without synthetic fungicides.The research, conducted at the University of Muhammadiyah Malang, used a split-plot design with two factors: biological pesticides (Tricogreen, Natural Glio, Trico-G) and liquid organic fertilizers (rabbit urine POC, shrimp shell MOL, banana hump MOL). The experiment had nine treatment combinations with three plant samples each. Results showed that biological pesticides significantly reduced Sigatoka disease intensity, with the J3P3 treatment (Trico-G and Banana Hump MOL) achieving the lowest infection rate of 29.55%, reducing disease intensity by 70.45%. Liquid organic fertilizers also improved plant growth, increasing leaf number and leaf area. This indicates that biological agents and organic fertilizers effectively manage Sigatoka disease and promote healthy banana plant growth.